2019
DOI: 10.1155/2019/9438089
|View full text |Cite
|
Sign up to set email alerts
|

Bithalamic Infarction (Artery of Percheron Occlusion) after Anterior Cervical Discectomy and Fusion

Abstract: Bithalamic infarction resulting from occlusion of the artery of Percheron after cervical spine surgery is a rare pathological entity. Diagnosis and early detection are challenging. Prompt management may help to improve the outcome. We present a case of a 39-year-old male patient, smoker, diagnosed with multiple cervical disc herniations, who underwent Anterior Cervical Discectomy and Fusion (ACDF) for C3-C4, C4-C5, and C5-C6. During the 2-hour and 50-minute surgery, the patient was lying supine with his neck h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…On May 27, 2020, a personal literature review based on a 2015-2020 PubMed search [key items: "artery of Percheron" AND ("case report" OR "case-series")] found 73 papers published in English language (30, 37, and 6 papers included females, males, and both sexes, respectively). Among the 37 studies including only males, 13 reported sleepiness or equivalent terms (i.e., hypersomnolence, drowsiness, or excessive daytime sleepiness) as a delayed complication of an AOP stroke (Table 1; Afana et al, 2019;Aryan et al, 2016;Bailey & Khadjooi, 2016;Goico & Mikesell, 2018;Harisuthan et al, 2018;Ince & Asan, 2018;Kamasak et al, 2015;Khanni et al, 2018;Oliveira et al, 2018;Shah & Ali, 2018;Vasconcellos et al, 2016;Zelante et al, 2015;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On May 27, 2020, a personal literature review based on a 2015-2020 PubMed search [key items: "artery of Percheron" AND ("case report" OR "case-series")] found 73 papers published in English language (30, 37, and 6 papers included females, males, and both sexes, respectively). Among the 37 studies including only males, 13 reported sleepiness or equivalent terms (i.e., hypersomnolence, drowsiness, or excessive daytime sleepiness) as a delayed complication of an AOP stroke (Table 1; Afana et al, 2019;Aryan et al, 2016;Bailey & Khadjooi, 2016;Goico & Mikesell, 2018;Harisuthan et al, 2018;Ince & Asan, 2018;Kamasak et al, 2015;Khanni et al, 2018;Oliveira et al, 2018;Shah & Ali, 2018;Vasconcellos et al, 2016;Zelante et al, 2015;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the search results of Google Scholar, only three case reports of acute cerebral infarction following cervical spine surgery have been published[ 3 - 5 ]. Afana et al [ 3 ] deemed that intraoperative surgical manipulation, hypotensive anesthesia, and prolonged neck hyperextension might contribute to their patients’ stroke.…”
Section: Discussionmentioning
confidence: 99%
“…According to the search results of Google Scholar, only three case reports of acute cerebral infarction following cervical spine surgery have been published[ 3 - 5 ]. Afana et al [ 3 ] deemed that intraoperative surgical manipulation, hypotensive anesthesia, and prolonged neck hyperextension might contribute to their patients’ stroke. Graffeo et al [ 5 ] expressed similar sentiments and speculated that the true incidence of cerebral ischemia might be underestimated by current reports, particularly in the delayed setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 49 54) Other factors, including instrumentation, probe maneuver for lateral exploration, cautery dissection, and prolonged neck hyperextension induce VAI. 2 34 58) Drilling was the most frequent cause of VAIs in previously reported cases. 20) Therefore, surgeons should be prudent when drilling the uncovertebral joint or neural foramen, and avoid coarse extensive lateral drilling.…”
Section: Iatrogenic Vai According To Surgical Approachesmentioning
confidence: 91%